Fungsi Edukasi pada Sastra Lisan Iabhanti Watulea dalam Masyarakat Watulea, Kabupaten Buton Tengah Provinsi Sulawesi Tenggara - Sarifudin Detikoa (Program Magister Linguistik Universitas Udayana, 2017)
Kabhanti Watulea is oral literature of Watulea society in District Gu, Central Buton, Southeast Sulawesi Province. Kabhanti Watulea is an old literary works that are bound and has a distinctive shape. Kabhanti Watulea contains messages about social criticism comes as a form of dissatisfaction with the reality of inequality in society Watulea. The social criticism includes educational functions, as a form of learning that is valuable to society Watulea. This study used a qualitative descriptive method to find the facts, circumstances, and phenomena. The data source is a verbal text Kabhanti Watulea. Data obtained after through observation, interviews, and the recording process. Data is transcribed and transliterated by informants and researchers into Indonesian language, then, analyzed by using the theory of functions to find educational functions. These findings, not off to do with the approach of sociology of literature. Educational function found is a function of the mating polyandry education, education of the law of karma, education of the providence of God, and the education of religious teachings.